β-Adrenergic receptor signaling in prostate cancer - Braadland, Peder R.; Ramberg, Håkon A.; Grytli, Helene H.; Taskén, Kristin A. (Frontiers in Oncology, 2015)
Enhanced sympathetic signaling, often associated with obesity and chronic stress, is increasingly acknowledged as a contributor to cancer aggressiveness. In prostate cancer, intact sympathetic nerves are critical for tumor formation, and sympathectomy induces apoptosis and blocks tumor growth. Perineural invasion, involving enrichment of intra-prostatic nerves, is frequently observed in prostate cancer and is associated with poor prognosis. β2-adrenergic receptor, the most abundant receptor for sympathetic signals in prostate luminal cells, has been shown to regulate trans-differentiation of cancer cells to neuroendocrine-like cells and to affect apoptosis, angiogenesis, EMT, migration and metastasis. Epidemiologic studies have shown that use of β-blockers, inhibiting β-adrenergic receptor activity, is associated with reduced prostate cancer specific mortality. In this review we aim to present an overview on how β-adrenergic receptor and its downstream signaling cascade influence the development of aggressive prostate cancer, primarily through regulating neuroendocrine differentiation.